INTELLECTUAL CULTURE OF DIGITAL SOCIETY: A PHILOSOPHICAL ANALYSIS (Scientific journal of the Fergana State University, 2023)
In the modern world, digitalization, increasing informatization, the development of the ability to influence human consciousness and even our decision-making based on neuroscience and artificial intelligence, changes in culture cause, completely new structural changes that have not been observed before in social development. This article philosophically analyzes the essence of intellectual culture and the specific characteristics of intellectual culture in a digital society.